2020
DOI: 10.18502/ijph.v49i11.4728
|View full text |Cite
|
Sign up to set email alerts
|

Association between Facebook Use, Depression and Family Satisfaction: A Cross-Sectional Study of Romanian Youth

Abstract: Background: In recent years, Facebook has increasingly become an essential part of the lives of people, particularly youths, thus many research efforts have been focused on investigating the potential connection between social networking and mental health issues. This study aimed to examine the relationship between Facebook use, emotional state of depression, and family satisfaction. Methods: This study used the online survey created in Google Docs on the Facebook ‘wall’, as research method. The survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Culture and socialisation might play an important role in shaping children’s judgement about couple situations, as they see models of couple interactions in their families, in the media, and real-life situations. In addition, the present research refers to an imagined love-based situation, which might activate children’s memories about what they have socially learned in their families about living as a couple [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Gender and Helping Behaviour In Couple Relationshipsmentioning
confidence: 99%
“…Culture and socialisation might play an important role in shaping children’s judgement about couple situations, as they see models of couple interactions in their families, in the media, and real-life situations. In addition, the present research refers to an imagined love-based situation, which might activate children’s memories about what they have socially learned in their families about living as a couple [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Gender and Helping Behaviour In Couple Relationshipsmentioning
confidence: 99%
“…Iovu i wsp. [8] wykazali, że wysoki stopień aktywności członków rodziny na Facebooku ma negatywny wpływ na poziom ich satysfakcji z życia. Przeciwnie Sharaievska i Stodolska [9] informują, że korzystanie z portali społecznościowych zwiększa satysfakcję rodziny, umożliwiając uczestnikom pozostawanie w kontakcie z dalszymi jej członkami oraz pozwala rozwijać poczucie wspólnoty.…”
Section: Wstępunclassified
“…In their opinion, the misunderstandings might be due to differences in family members' views on the role of technology, the length of time young people can spend using SNS, the ways SNS are used and their impact on children. Iovu et al [8] showed that a high level of activity of family members on Facebook had a negative impact on the level of their satisfaction with life. A contrasting finding was reported by Sharaievska and Stodolska [9], who observed that the use of SNS increased a family's satisfaction, allowing family members to stay in touch with more distant relatives and develop a sense of community.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the relationship between depressive symptoms and addiction to SNs, there are many studies based on applying the first measure of addiction to the internet ( Young, 1998 ), and the results consistently show positive correlations between the two phenomena ( Zhang et al, 2015 ; Becoña, 2016 ; Błachnio et al, 2016 ; Hussain and Griffiths, 2018 ; Peris et al, 2018 ; Iovu et al, 2020 ). Therefore, it is expected that this study will find similar results.…”
Section: Introductionmentioning
confidence: 96%